MASIH TERBUKANYA PELUANG PENELITIAN PROSES CARON UNTUK MENGOLAH LATERIT KADAR RENDAH DI INDONESIA - Prasetiyo, Puguh; Nasoetion, Ronald (Jurnal Metalurgi, 2011)
Indonesia had the resources of nickel at the second in the world. The resources are nickel oxide which said laterite. The abundant of laterite locate at Sulawesi Tenggara (South-East Sulawesi) and Halmahera. There are two main mineral in laterite, limonit contains Ni<1,5% and saprolit contains Ni>1,5%. The high grade nickel saprolit contains Ni>1,8% has been processed in Sulawesi Tenggara to produce FeNi (ferro nickel) in Pomalaa by PT Antam, and to produce Ni-matte (nickel matte) in Sorowako by PT INCO Canada. The low grade laterite (limonit and saprolit contains Ni<1,8%) not yet processed in Indonesia. To process the low grade laterite are used Caron’s process or HPAL’s process (High Pressure Acid Leaching). The condition of laterite’s ores are used to choice the process. The Caron’s process is remained after 1990’s because it consume high energy with low metal recovery (Ni : 70 – 80 % Co max 50 %). The choice to process low gradelaterite is HPAL because it consume low energy wiyh high recovery of metal (Ni > 90 % and Co > 90 %). The fact three HPAL plant in Australia unsuccessful (Bulong closed on 2003, Cawse closed on 2008, and Murrin Murrin taked over by Minara and change to heap leach on 2007) and the Caron plant still exist in Cuba (Nicaro and Punta Gorda), Queensland Nickel di Australia, and Tocantin Brasilia. Then Caron’s process still have opportunity to process the low grade laterite in Indonesia if the recovery of metal can be increase as same as HPAL and the consume of energy can be decreased.